‘Digital surveillance’ from the perspective of ‘Christian Freedom’ : a theological assessment in conversation with Martin Luther and Dietrich Bonhoeffer - Simon, Christiane J. (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.